Deepwater Indo-Pacific species of the snake-eel genus Ophichthus (Anguilliformes: Ophichthidae), with the description of nine new species - Mccosker, John E. (Zootaxa, 2010)
The 19 Indo-Pacific species of the snake-eel genus Ophichthus (family Ophichthidae, subfamily Ophichthinae) that live at or below 200 m are reviewed. Included are: Ophichthus aphotistos, O. brachynotopterus, O. echeloides, O. exourus, O. genie, O. kunaloa, O. megalops, O. mystacinus, O. serpentinus, O. urolophus, and nine new species which are described: O. alleni from 115–200 m off eastern Australia; O. aniptocheilos from 391–421 m off Tonga; O. congroides from 300 m off the Tuamotu Islands; O. hirritus from 600 m off the Seychelle Islands; O. humanni from 254–300 m off Vanuatu; O. ishiyamorum from 258–400 m off the Gulf of Aden, Somalia; O. lentiginosus from 400 m off Vanuatu and New Caledonia; O. microstictus from 362–450 m off Tonga, Fiji, and possibly New Caledonia; and O. tomioi from 300– 423 m off the Philippines, Marquesas, Fiji, and the Seychelle Islands. The range and depth distributions of the following are expanded to include: O. brachynotopterus to New Caledonia and Vanuatu between 541–580 m; O. mystacinus to Tonga, Fiji, and the Philippines between 371–824 m; and O. urolophus to Western Australia and Indonesia between 40– 420 m. An identification key is provided. Characteristics and the behavior of species of the subgenus Coecilophis, to which all treated species except O. aphotistos belong, is discussed. Ophichthys madagascariensis Fourmanoir (1961) is proposed to be a junior synonym of Pisodonophis cancrivorus (Richardson 1848).